DNA Barcoding for the Identification of Botanicals in Herbal Medicine and Dietary Supplements: Strengths and Limitations - Parveen, Iffat; Gafner, Stefan; Techen, Natascha; Murch, Susan J.; Khan, Ikhlas A. (Planta Medica, 2016)
In the past decades, the use of traditional medicine has increased globally, leading to a booming herbal medicine and dietary supplement industry. The increased popularity of herbal products has led to a rise in demand for botanical raw materials. Accurate identification of medicinal herbs is a legal requirement in most countries and prerequisite for delivering a quality product that meets consumer expectations. Traditional identification methods include botanical taxonomy, macroscopic and microscopic examination, and chemical methods. Advances in the identification of biological species using DNA-based techniques have led to the development of a DNA marker-based platform for authentication of plant materials. DNA barcoding, in particular, has been proposed as a means to identify herbal ingredients and to detect adulteration. However, general barcoding techniques using universal primers have been shown to provide mixed results with regard to data accuracy. Further technological advances such as mini-barcodes, digital polymerase chain reaction, and next generation sequencing provide additional tools for the authentication of herbs, and may be successful in identifying processed ingredients used in finished herbal products. This review gives an overview on the strengths and limitations of DNA barcoding techniques for botanical ingredient identification. Based on the available information, we do not recommend the use of universal primers for DNA barcoding of processed plant material as a sole means of species identification, but suggest an approach combining DNA-based methods using genus- or species-specific primers, chemical analysis, and microscopic and macroscopic methods for the successful authentication of botanical ingredients used in the herbal dietary supplement industry.
Keywords: DNA barcoding; dietary supplements; herbal medicine; mini-barcodes